The Health and Economic Impacts of Structural Energy Performance Investments in Wales: An Evaluation of the Arbed Programme - Rhodri Johnson; Sarah Rodgers; Alan Watkins; Wouter Poortinga; Charlotte Grey; Shiyu Jiang; Pippa Anderson; Ronan A Lyons (International Journal of Population Data Science, 2017)
ABSTRACT